1992
DOI: 10.1128/jcm.30.7.1621-1624.1992
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vancomycin resistance in Enterococcus species

Abstract: Enterococcusfaecalis and Enterococcusfaecium isolates that are resistant to vancomycin have recently been identified in North America and Europe. Of 155 clinical isolates of enterococci (113 E. faecium and 42 E. faecalis), we found that 98 were resistant, 52 were moderately susceptible, and 5 had intermediate susceptibilities to vancomycin by using broth microdilution susceptibility testing according to the National Committee for Clinical Laboratory Standards (NCCLS) (Approved Standard M7-A2). Using NCCLS disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 22 publications
2
54
1
Order By: Relevance
“…The improved current results probably reflect use of the 1992 NCCLS revised procedure. In our survey, the automated systems performed well and we did not confirm an earlier finding [27] that the Vitek GPS-TA card exhibited only 72% sensitivity for the detection of vancomycin resistance. Lack of sensitivity was thought to be due to insufficient growth in the wells.…”
Section: Discussioncontrasting
confidence: 99%
“…The improved current results probably reflect use of the 1992 NCCLS revised procedure. In our survey, the automated systems performed well and we did not confirm an earlier finding [27] that the Vitek GPS-TA card exhibited only 72% sensitivity for the detection of vancomycin resistance. Lack of sensitivity was thought to be due to insufficient growth in the wells.…”
Section: Discussioncontrasting
confidence: 99%
“…These are the vanA strains, which show high-level vancomycin resistance (MICs of Ͼ32 g/ml) and resistance to teicoplanin; vanB strains, which have variable resistance to vancomycin (MICs of 4 to Ն128 g/ml) and susceptibility to teicoplanin; and vanC motile strains, which show intrinsic resistance to low levels of vancomycin (MICs of 2 to 32 g/ml) and susceptibility to teicoplanin. From studies of vancomycin resistance, Willey et al showed the MicroScan Positive MIC Type 6 panels to have a sensitivity and specificity of 99 and 96%, respectively, when the visual inspection method of detection is used (27). In addition, other studies have shown these panels to be reliable except in cases in which low-level vancomycin resistance (MICs of 4 to 8 g/ ml) was present (22).…”
Section: Discussionmentioning
confidence: 99%
“…Automated systems, including the Vitek and MicroScan systems, have been developed to identify and to determine the antimicrobial susceptibility of enterococci (1,2,18,22,23,(25)(26)(27)(28). Previous studies have shown conventional MicroScan panels to be reliable in the identification of Enterococcus spe-cies, even though the data bank includes only E. faecalis, E. faecium, E. durans, and E. avium (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only 35% of respondents used this agar, and 28% used Mueller-Hinton agar inappropriately. Although the original description of the vancomycin screening test reported the use of Mueller-Hinton agar, this was only a preliminary study, which was stated to require further evaluation [22]. The original method was optimised subsequently, and brain-heart infusion agar was found to be superior to Mueller-Hinton agar [23].…”
Section: Discussionmentioning
confidence: 99%